Measurement of Environmental Concern: A Review and Analysis - Cruz, Shannon M.; Manata, Brian (Frontiers in Psychology, 2020)
Recent growth in the subdiscipline of environmental communication has provided many new opportunities for applied communication research in environmental contexts. For authors studying environmental concern or attitudes, however, survey development can be a daunting task. A large number of scales measuring environmental concern have been developed, and it can be challenging to make informed decisions about which to use. To assist authors in navigating the literature, we present a review of existing scales, followed by two studies in which we examine the structural validity of five scales that are commonly implemented in this corpus. These results have important implications for general issues with measurement in this area, and inform our recommendations for authors about key considerations when selecting and using environmental concern scales.